ANALISIS KESULITAN SISWA MENYELESAIKAN SOAL OLIMPIADE MATEMATIKA SMP - Sahroni, Ade; Soebagyo, Joko (International Journal of Progressive Mathematics Education, 2024)
This study aims to find out the description of students' difficulties in solving math olympiad questions at SMP Negeri 2 Muaragembong. This research is a descriptive study with a qualitative approach designed to find out the description of students' difficulties in solving Olympic questions. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the study, it was stated that the difficulties in solving Olympic questions consisted of four types of difficulty components, namely conceptual difficulties, principle difficulties, information difficulties and arithmetical difficulties. Internal factors include students' lack of interest in learning mathematics, especially in linear programming material, study routines, and lack of motivation to learn. While external factors include family and school environment. Efforts that can be made to reduce students' difficulties in solving Olympic questions based on the difficulties experienced and the causative factors behind them include: providing a better understanding to students, students actively asking questions, and using learning media